The first issues of Gordian III (238-244 a. D.) and the opening of Viminacium mint in Upper Moesia - Royo Martínez, María del Mar (Documenta & Instrumenta - Documenta et Instrumenta, 2022)
In this paper we analyze the oldest issues of one of the first emperors of the so-called crisis of the third century: Gordian III (238-244 A.D.). During the first years in which he was at the head of the empire, under the tutelage of his mother Maecia Faustina and her circle of advisers, some transformations took place in the administration and in fiscal and monetary matters. One of them was the creation of the Viminacium mint, in the Balkan province of Lower Moesia. In this article, both the possible causes that determined its opening and the consequences of its foundation, will be studied.